Fire effects on invasive and native warm‐season grass species in a North American grassland at a time of extreme drought. Issue 4 (7th May 2015) - Havill, Scott; Schwinning, Susanne; Lyons, Kelly G.; Fraser, Lauchlan
Abstract Question Can the timing of cutting or burning be used to selectively damage an invasive C4 grass species while limiting collateral damage to dominant native C4 grass species in a grassland community? Location A medium to short grass prairie in central Texas, US. Methods We conducted six cut and burn trials between June 2011 and January 2012 during an exceptional drought year. Target species were the native, perennial, C4 grass Schizachyrium scoparium (little bluestem) and the introduced, perennial, C4 grass Bothriochloa ischaemum (yellow bluestem). Burn trials were conducted inside a steel barrel using standardized fuel loads. To assess recovery, we counted the first cohort of new tillers that emerged after treatment and tillers that grew in the subsequent spring. We also recorded phenological status, meteorological variables and burn temperatures to determine if tiller recovery was predictable. Results Bothriochloa ischaemum responded more negatively to burning than to cutting, but these treatments were no different for S. scoparium. Both species produced the smallest number of tillers after the summer burns, and the burn date × species interaction was insignificant. On average, peak fire temperature inside tussocks was 100 °C higher in B. ischaemum than in S. scoparium. Judging from the reduction in tiller densities in undisturbed plots from spring 2011 to spring 2012, B. ischaemum was also more sensitive to drought. Multivariate models were significant and related burn recovery to peak fire temperature, among other factors, and recovery from cutting to ambient temperature on the day of cutting. In B. ischaemum, plants with higher investment in early reproductive growth suffered more burn damage. Conclusions We identified no optimal burn time that maximized discrimination between the two species. Nonetheless, the invasive species was more sensitive to both drought and fire, possibly due to higher heat exposure of growing points. Thus, burning during the summer of a drought year may constitute the sought‐after treatment that selectively favours native species. Ultimately, successful management will involve fuel and temperature management combined with assessment of the relative phenologies of the target species prior to burning. This study suggests that a hot fire at a time when the invasive species has a larger investment in early reproductive growth will provide the best control.